Psychological conditions of forming general skills of business communication in students - Korotayeva, I.; Pohozhina, I.; Frolova, E. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article repoesents the problems of human existance on different levels of socialization. There was made an accent on necessity of increasing spiri- tua-moral principles of society development as a quarantee of success of social-economic transformations in the country.